The Decision Understanding of Contraception Usage on Fertile Age Couple in Terjun Village - Fitria, Aida (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Total Fertility Rate in North Sumatera is enough high reach until 3 % thatindicate increasing of fertility rate. The woman chance for fertilying and boringmakes the woman to illness and even the death. So, it is necessary to move upfertile couple age participation more in using contraception for along time. Therate of fertile couple age in Terjun area at 2013 is about 1.863 persons (37,5%).The research to analyze the process of making decision fertile couple agein using contraception. This research used qualitative methode with interpretiveparadigama. This research was done in Terjun area District Medan Marelan fromJanuary 2013 to April 2014. The informan in this research were the every personswho knows and also take part in using contraception. Such as, fertile couple age(PUS) staff KB in Terjun, friends, and other families. The data collected byinterviewing and observation. The real data test by validating test and datarealibilty.The result of research showed that in making decision contraception usage,fertile age couple (FAC) consider their decision first by analising some importantaspects relate with religion and the efect to their health. The culture in aroundthem, and also economy aspect and accessibilitas of methode. Taking decision forfertile couple age we know that there were three (3) type of decision. The decisionof husband-wife with his wife herself to become an acceptor, decision husbandwife with her husband himself to be an acceptor, decision husband only with hiswife become acceptor.The need for a lot of activities that can empower the public perception thatbusiness planning is not a matter forwomenalone. Foritis expected that stakeholders such as NGOs (NGO) said that the Board andother relevant agenciesto bemore focused and concerned to deal with these problems by providingopportunities for women to acquire good knowledge about contraceptives. Thevillage governmentis also expected to improve access and quality of information,education, counseling and contraceptive services provided to the fertile couplesage through the advocacy of health workers who are skilled and friendly. Thepresence of approaches to religious leaders and community leaders to worktogether in an effort to increase the use of contraceptionin fertile age couplesneeds tobe increased again.